Empowering communication and media studies students: the MCSC journey / Siti Suraya Subarman - Subarman, Siti Suraya (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Since its inception in 2017, the Media and Communication Student Club (MCSC) at UiTM Cawangan Negeri Sembilan Kampus Rembau has been a cornerstone of support and growth for students pursuing a Diploma in Media and Communication Studies. This club serves as a dynamic platform for students to collaborate, learn, and contribute to the vibrant academic environment at UiTM Cawangan Negeri Sembilan Kampus Rembau. At the helm of MCSC are five dedicated advisors Madam Farah Hazween, Sir Muhammad Nabihan, Sir Ahmad Syakir, Miss Wan Anis Aqilah, and Madam Amirah. These advisors play a crucial role in guiding MCSC members, offering insights, and ensuring the smooth operation of the club’s activities. Their consistent guidance has been instrumental in nurturing an atmosphere of creativity and learning within the club. MCSC operates with a structured leadership system, led by a high council in 2023/2024 comprising passionate and dedicated individuals who oversee various aspects of the club’s functioning. President Arriesha Nabilah, a dynamic third semester Masscomm student, leads MCSC with inspiration, fostering a supportive and growth-oriented environment.